The blade itself - Abercrombie, Joe (Abercrombie, Joe. First law, 2015)
Infamous Logen Ninefingers has finally run out of luck. Caught in one feud too many, he's on the verge of becoming a dead barbarian. He is caught in murderous conspiracies and old scores, along with Captain Jezal dan Luthar, Inquisitor Glokta and the wizard Bayaz, who all must try to survive the coming war.